EFEKTIVITAS MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMAMPUAN KONEKSI MATEMATIS - rahmat swandi siregar; Muhammad Syahril Harahap (JURNAL MathEdu (Mathematic Education Journal), 2019)
The aims of this study is to describe the effectiveness of using flipped classroom learning model on mathematical connections ability on the eighth grade students of SMP Negeri 3 Padangsidimpuan. This research was conducted by applying experimental method with 27 students as the sample and they were taken by using cluster sample technique from 222 students. Test and observation were used in collecting the data. Based on descriptive analysis, it was found (a) the average of using flipped classroom learning model was 3.80 (very good category) and (b) the average of mathematical connections ability before using flipped classroom learning model was 51.6037 (fair category) and after using flipped classroom learning model was 81.6519 (very good category). Furthermore, by using pair sample ttest and help SPSS version 22, the result showed the significant value was less than 0.05 (0.000<0.05). It means, by using flipped classroom learning model on mathematical connections ability on the eighth grade students of SMP Negeri 3 Padangsidimpuan.